Diagnosis of fungal opportunistic infections in people living with HIV from Guatemala and El Salvador. Issue 12 (29th September 2021) - Forno, Diana; Samayoa, Blanca; Medina, Narda; Arathoon, Eduardo; Mejia, Carlos Rodolfo; Gordillo, Remei; Cedillos, Rolando; Rodas, Jose; Ahlquist Cleveland, Angela; Chiller, Tom; Caceres, Diego H.
Abstract: Objectives: Histoplasmosis and cryptococcosis are important public health problems in people living with HIV (PLHIV) in Central America. Conventional laboratory tests, such as culture and microscopy, are not optimal; however, antigen (Ag) tests are rapid, highly sensitive, and specific for diagnosis of fungal opportunistic infections (OI). The aim of this study was to describe the results of a laboratory‐based surveillance system for histoplasmosis and cryptococcosis. Methods: An observational cross‐sectional study based on laboratory surveillance, was carried out in two hospitals in Guatemala and one hospital in El Salvador, between July 2012 and December 2014. Diagnosis of histoplasmosis and cryptococcosis in PLHIV were performed by culture and Ag test. Results: A total of 160 PLHIV were diagnosed with fungal OI, of which, 96 (60%) were diagnosed with histoplasmosis, 62 (39%) were with cryptococcosis, and two patients (1%) were diagnosed with both fungal diseases. Of the 160 patients analysed in this study, 94 (59%) were diagnosed using only an Ag assay. CD4 cell count data were available for 136 (85%) patients; 127 (93%) patients had a CD4 count <200; and 90 (66%) had counts <50 CD4 cells per µl. Antiretroviral therapy utilisation at diagnosis was low (33%). Seventy‐one out of 160 (44%) were co‐infected with tuberculosis or other OIs. Conclusion: More than half of the patients in this study were diagnosed only by rapid laboratory Ag tests. A high per cent of the patients had advanced HIV disease.